A proposed model for evaluating the organization and management of time among farmers in applying agricultural practices / Nineveh Governorate (Literature review study) - Younis, Asmaa Zuhair; Hasan, Anhar Mohammed Ali; Mahal, Mohammed Ahmed (Journal of agricultural, environmental and veterinary sciences, 2025)
The main objectives of the article were to evaluate the time management practices of the farmers by objectives: Building a model for organizing & managing of the time among farmers in applying agricultural practices/ Nineveh Governorate; identifying importance of the organizing & dividing time in managing of agricultural practices; & identifying methods for time management during the agricultural seasons, then descriptive approach was adopted as a basic approach in this study, then to achieve the research objectives; we relied entirely on the review of literature & articles (purely literary review) although there are many studies which done in this domain were (10) studies, there is lack of orient toward this matter although it’s important, as a primary source of the research data. Previous studies related to topic of time management were selected (based on the focusing on organizational; sequential and administrative time research).Most important results achieved: steps were developed to the develop a model for organizing farmers' time which including: evaluating current time use setting time limits for implementing agricultural activities & practices; creating a list of the assigned tasks & obligations for farmers; grouping related tasks; planning the day; focusing on difficult tasks first; making organization a habit & allocating free time between the tasks to achieve second goal, the importance of organizing & dividing time to manage agricultural practices was identified, to achieve third goal: determining methods for the managing time during agricultural season goals were set to increase agricultural production correctly using “SMART” method when setting goals, prioritize agricultural practices wisely, the define tasks based on this importance & urgency, set an important specific time to complete the work, and the most benefits of the time management in Nigeria is keeping sustainable development, and using agricultural resources about ratio of 70% and depend on liner software.
Keywords: Effective time management; calendar; organization; Nineveh Governorate